Introduction to wireless digital communication : a signal processing perspective / Robert W. Heath, Jr. - Heath, Robert W., Jr, 1973- (Prentice Hall, 2017)
Developed and proven as part of a special laboratory course at the University of Texas, this unique text makes wireless communication accessible both to undergraduates and to practicing electrical engineers who haven't specialised in communications.